Profiles of Nature Exposure and Outdoor Activities Associated With Occupational Well-Being Among Employees - Hyvönen, Katriina; Törnroos, Kaisa; Salonen, Kirsi; Korpela, Kalevi; Feldt, Taru; Kinnunen, Ulla (Frontiers in Psychology, 2018)
This research addresses the profiles of nature exposure and outdoor activities in nature among Finnish employees (N = 783). The profiles were formed on the bases of nature exposure at work and the frequency and type of outdoor activities in nature engaged in during leisure time. The profiles were investigated in relation to work engagement and burnout. The latent profile analysis identified a five-class solution as the best model: High exposure (8%), Versatile exposure (22%), Unilateral exposure (38%), Average exposure (13%), and Low exposure (19%). An Analysis of Covariance (ANCOVA) was conducted for each well-being outcome in order to evaluate how the identified profiles related to occupational well-being. Participants with a High, Versatile, or Unilateral exposure profile reported significantly higher work engagement in the dimensions of vigor and dedication than did the participants with a Low exposure profile. The participants with the High exposure profile also reported lower burnout in the dimensions of cynicism and professional inadequacy than the participants with the Low exposure profile. Nature exposure during the workday and leisure time is an underresearched but important aspect in promoting occupational well-being. Keywords: nature exposure, outdoor activities, work engagement, burnout, employees